Emotional Intelligence and Adolescent Risk Behavior: A Systematic Review. - Sánchez-López, María T.; Fernández-Berrocal, Pablo; Gómez-Leal, Raquel; Megías-Robles, Alberto (My University, 2023)
Objective of the study: Risky behavior implies a series of negative consequences in peoples lives as it poses a threat to well-being, health and safety. It is essential to search for those variables that can alleviate these effects. Its study becomes especially relevant in the period of the life cycle from pre-adolescence to early adulthood, as this is a period in which this behaviour is highly prevalent. Among others, one variable that has received special attention as a protective variable is emotional intelligence, that is, the ability to perceive, use, understand and regulate emotions. The aim of this study is to conduct a systematic review of the evidence available to date on the relationship between risk behavior and emotional intelligence in this population. Methodology: The databases used were PsycINFO, Scopus and PubMed. A total of five articles were found, comprising a sample of 1901 participants aged between 13 and 19 years and measuring emotional intelligence through self-report instruments. Results obtained: Emotional intelligence in adolescents was positively related to risk-prevention behaviours, while it was negatively related to all dimensions of risk behavior. A single study found a negative relationship between risk behavior and one of the emotional intelligence abilities, the interpersonal ability. Conclusion: Future lines of research should focus on expanding the number of studies relating emotional intelligence and child and youth risk behaviors, as well as the use of objective measures of performance.
Keywords: Adolescentes - Psicología; Emotional intelligence; Risk behavior; Adolescents; Systematic review